2021
DOI: 10.1136/thoraxjnl-2021-217429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CRTH2 antagonism on the response to experimental rhinovirus infection in asthma: a pilot randomised controlled trial

Abstract: Background and aimsThe chemoattractant receptor-homologous molecule expressed on T helper type 2 cells (CRTH2) antagonist timapiprant improved lung function and asthma control in a phase 2 study, with evidence suggesting reduced exacerbations. We aimed to assess whether timapiprant attenuated or prevented asthma exacerbations induced by experimental rhinovirus (RV) infection. We furthermore hypothesised that timapiprant would dampen RV-induced type 2 inflammation and consequently improve antiviral immune respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…In a Phase II study that employed an experimental RV challenge of patients with asthma, DP2 antagonism did not affect exacerbation severity and of note, the investigators reported a negative correlation between PGD2 levels during RV infection and prescribed ICS dose. 35 This observation and our findings would suggest that combining a DP2 antagonist with a DP1 agonist or a drug that induces endogenous PGD2, such as a TLR7 ligand, would elicit a more favourale outcome.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In a Phase II study that employed an experimental RV challenge of patients with asthma, DP2 antagonism did not affect exacerbation severity and of note, the investigators reported a negative correlation between PGD2 levels during RV infection and prescribed ICS dose. 35 This observation and our findings would suggest that combining a DP2 antagonist with a DP1 agonist or a drug that induces endogenous PGD2, such as a TLR7 ligand, would elicit a more favourale outcome.…”
Section: Discussionsupporting
confidence: 62%
“…16 Our study highlights that the effectiveness of DP2 antagonism is critically dependent on the production of endogenous PGD2, and thus the inhibitory effects of steroids on COX2 activity and expression may have counteracted the positive effects of DP2 antagonism in some patients, potentially explaining the mixed success of the various Phase II and III trials. 918,35 Our findings revealed that DP2 antagonism in the absence of a RV-induced exacerbation has no benefit and that dual DP2 antagonism/steroid therapy is ineffective. Paradoxically, these observations suggest that therapy with a DP2 antagonist would work best in those patients who frequently exacerbate (given the need for endogenous PGD2), who are poorly compliant with their ICS/OCS therapy, or whose steroid insensitivity/resistance fails to dampen the production of PGD2.…”
Section: Discussionmentioning
confidence: 73%
“…in 2021 found that OC-459 treatment had little impact on the clinicopathological changes induced by rhinovirus RV-A16 infection in patients treated with inhaled corticosteroids, though the same study also concluded that OC-459 was safe and well-tolerated [76].…”
Section: Astrazeneca Analoguesmentioning
confidence: 98%
“…Of note, the structure included in this review has not been confirmed by Oxagen, but was characterized as OC-459 by Amira. In addition, although Pettipher et al were the first to publish a non-clinical study of OC-459, it appears that the unpublished development of OC-459 had already been undertaken by other parties [ 73 , 74 , 75 , 76 , 77 , 78 ].…”
Section: Indole-based Potential Gpr44 Analoguesmentioning
confidence: 99%
See 1 more Smart Citation